Ambush at Central Park : When the IRA Came to New York - Bulik, Mark (Book collections on Project MUSE., 2023)
"A compelling, action-packed account of the only officially sanctioned I.R.A attack ever conducted on American soil In 1922, three of the Irish Republican Army's top gunmen arrived in New York City seeking vengeance. Their target: "Cruxy" O'Connor, a young Irishman who kept switching sides as revolution swept his country in the wake of World War I. Cruxy's last betrayal dealt a stunning blow to Ireland's struggle for independence: six of his I.R.A. comrades were killed when he told police the location of their safe house outside Cork. A year later, the I.R.A. gunned him down in a hail of bullets before a crowd of horrified New Yorkers at the corner of 84th Street and Central Park West. Based primarily on first-hand accounts, most of them never before published, Ambush at Central Park is a cinematic exploration of the enigma of "Cruxy" O'Connor: Was he really a decorated war who became a spy for Britain? When he defected to the I.R.A., did his machine gun really jam in a crucial attack? When captured, did he give up his I.R.A. comrades only under torture? Was he a British spy all along? Or was he pursuing a decades-old blood feud between his family and that of one of his comrades? A longtime editor at The New York Times, author Mark Bulik delved through Irish government archives, newspaper accounts, census data, and unpublished material from the families of the main actors. Together they add to the sensational story of a rebel ambush, a deadly police raid, a dinner laced with poison, a daring prison break, a boatload of Tommy guns on the Hoboken waterfront, an unlikely pair of spies who fall in love, and an audacious assassination plot against the British cabinet. Gravely wounded and near death, Cruxy refused to cooperate with the detectives investigating the case. And so, the spy who stopped spying and the gunman who stopped shooting became the informer who wouldn't inform, even at death's door. Here is a forgotten chapter of Irish and New York history: the story of the only officially authorized I.R.A. attack on American soil"--